Plato and the divided self - Barney, Rachel, 1966-; Brennan, Tad, 1962-; Brittain, Charles (Cambridge ; Cambridge University Press, 2012)
'Plato's account of the tripartite soul is a memorable feature of dialogues like the Republic, Phaedrus and Timaeus: it is one of his most famous and influential yet least understood theories. It presents human nature as both essentially multiple and diverse - and yet somehow also one - divided into a fully human'rational' part, a lion-like'spirited part' and an'appetitive' part likened to a many-headed beast. How these parts interact, how exactly each shapes our agency and how they are affected by phenomena like eros and education is complicated and controversial. The essays in this book investigate how the theory evolves over the whole of Plato's work, including the Republic, Phaedrus and Timaeus, and how it was developed further by important Platonists such as Galen, Plutarch and Plotinus. They will be of interest to a wide audience in philosophy and classics'--
'With every day, and from both sides of my intelligence, the moral and the intellectual, I thus drew steadily nearer to that truth by whose partial discovery I have been doomed to such a dreadful shipwreck: that man is not truly one, but truly two. I say two, because the state of my own knowledge does not pass beyond that point. Others will follow, others will outstrip me on the same lines, and I hazard the guess that man will be ultimately known for a mere polity of multifarious, incongruous and independent denizens. Robert Louis Stevenson, Dr Jekyll and Mr Hyde1 Most of the papers in this volume originated at two conferences, one held in 2005 at the University of Toronto and one in 2006 at Cornell University.2 As organizers we then commissioned another seven papers in order to produce a much more wide-ranging, if still far from comprehensive volume.3 Philosophical accounts of the tripartite soul in Plato have traditionally focussed on the Republic: while that dialogue remains central to many of the papers in this volume, readers will also find discussions of other dialogues featuring soul-partition (including Sheffield on the Phaedrus, Lorenz on the Timaeus, and Brisson on the Laws) and other relevant psychological investigations (Dorion on the Gorgias, Vasiliou on the Phaedo, Sheffield on the Symposium, Moss on the Philebus). Also included are three case studies of uses of the tripartite theory within the later Platonic tradition (Opsomer on Plutarch, Schiefsky on Galen, and Emilsson on Plotinus). The reader will thus be able to judge to what extent these various sources present a constant, unitary theory - a unitary and stable Platonic Psychology - underlying the developments and revisions in Plato's thinking, and in the views of his successors'--
Machine generated contents note: Acknowledgements and notes; Editors' introduction Rachel Barney, Tad Brennan and Charles Brittain; Part I. Transitions to Tripartition: 1. Enkrateia and the partition of the soul in the Gorgias Louis-Andre; Dorion; 2. From the Phaedo to the Republic: philosophers, non-philosophers, and the possibility of virtue Iakovos Vasiliou; 3. The soul as a one and a many: Republic 436a8-439d9 Eric Brown; Part II. Moral Psychology and the Parts of the Soul: 4. Er{u3BF3} before and after tripartition Frisbee Sheffield; 5. Speaking with the same voice as reason: personification in Plato's psychology Rachana Kamtekar; 6. Psychic contingency in the Republic Jennifer Whiting; 7. Curbing one's appetites in Plato's Republic James Wilberding; 8. The nature and object of the spirited part of the soul Tad Brennan; 9. How to see an unencrusted soul: Republic X 611b-612a Raphael Woolf; Part III. Developments in Late Plato: 10. Pictures and passions in the Philebus and Timaeus Jessica Moss; 11. The cognition of appetite in Plato's Timaeus Hendrik Lorenz; 12. Soul and state in Plato's laws Luc Brisson; Part IV. Parts of Soul in the Platonic Tradition: 13. Plutarch on the division of the soul Jan Opsomer; 14. Galen and the tripartite soul Mark Schiefsky; 15. Plotinus and Plato on soul and action Eyj{u2BEC}fur K. Emilsson.
Includes bibliographical references ( p. 368-382 ) and index.
Includes bibliographical references and index.
Keywords: Plato; Soul; PHILOSOPHY / History & Surveys / Ancient & Classical